2018
DOI: 10.1109/mcom.2018.1800137
|View full text |Cite
|
Sign up to set email alerts
|

Block4Forensic: An Integrated Lightweight Blockchain Framework for Forensics Applications of Connected Vehicles

Abstract: Today's vehicles are becoming cyber-physical systems that do not only communicate with other vehicles but also gather various information from hundreds of sensors within them. These developments help create smart and connected (e.g., self-driving) vehicles that will introduce significant information to drivers, manufactures, insurance companies and maintenance service providers for various applications. One such application that is becoming crucial with the introduction of self-driving cars is the forensic ana… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
166
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 249 publications
(166 citation statements)
references
References 11 publications
(11 reference statements)
0
166
0
Order By: Relevance
“…The Ethereum‐ControlChain ( E‐ControlChain ) was created as a ControlChain proof of concept to check ControlChain practical viability for the IoT. Their cost and performance analysis showed that even limited devices, like a Raspberry Pi, can easily handle the E‐ControlChain requirements. Cebe et al proposed Block4Forensic , which is a permissioned BC framework for managing the collected vehicle‐related data. Membership establishment and privacy is provided to the BC by a vehicular public key management (VPKI).…”
Section: Existing Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The Ethereum‐ControlChain ( E‐ControlChain ) was created as a ControlChain proof of concept to check ControlChain practical viability for the IoT. Their cost and performance analysis showed that even limited devices, like a Raspberry Pi, can easily handle the E‐ControlChain requirements. Cebe et al proposed Block4Forensic , which is a permissioned BC framework for managing the collected vehicle‐related data. Membership establishment and privacy is provided to the BC by a vehicular public key management (VPKI).…”
Section: Existing Workmentioning
confidence: 99%
“…Lightweight BC for resource-constrained devices 45,51,57 Consensus protocols 45,66,71 Scalability and processing overheads 51,59,63 Latency and throughput 46,72,73 Energy efficiency 45,74,75 Identity 74, [76][77][78] Auditability and accountability 33,75,79 BC-based authentication schemes 35 data without learning anything from them. Their system consists of record nodes and light nodes.…”
Section: Research Issue Research Workmentioning
confidence: 99%
“…KSI). Spoofing attack is mitigated by introducing an anonymous communication among nodes [8] and Keyless Signature Infrastructure (KSI) based distributed & witnesses trust anchor [30].…”
Section: Countermeasuresmentioning
confidence: 99%
“…Consider a scenario where an auto manufacturer sends an update instruction to a CAV owner and the CAV owner fails to execute the update instruction and an accident occurs due to that faulty sensor. In alternative proposals such as [24], storing the hash of the update instruction in the BC serves as proof that the auto manufacturer sent the instruction. However, there is no proof to show that the target CAV received and executed the update instruction.…”
Section: Nonrepudiationmentioning
confidence: 99%